Pulmonary exacerbations in patients with primary ciliary dyskinesia: an expert consensus definition for use in clinical trials - Lucas, Jane S; Gahleitner, Florian; Amorim, Adelina; Boon, Mieke; Brown, Philippa; Constant, Carolina; Cook, Simon; Crowley, Suzanne; Destouches, Damien M S; Eber, Ernst; Mussaffi, Huda; Haarman, Eric; et al. (ERJ open research, 2019)
Pulmonary exacerbations are a cause of significant morbidity in patients with primary ciliary dyskinesia (PCD) and are frequently used as an outcome measure in clinical research into chronic lung diseases. So far, there has been no consensus on the definition of pulmonary exacerbations in PCD. 30 multidisciplinary experts and patients developed a consensus definition for children and adults with PCD. Following a systematic review, the panel used a modified Delphi process with a combination of face-to-face meetings and e-surveys to develop a definition that can be used in research settings for children and adults with PCD. A pulmonary exacerbation was defined by the presence of three or more of the following seven items: 1) increased cough, 2) change in sputum volume and/or colour, 3) increased shortness of breath perceived by the patient or parent, 4) decision to start or change antibiotic treatment because of perceived pulmonary symptoms, 5) malaise, tiredness, fatigue or lethargy, 6) new or increased haemoptysis, and 7) temperature >38°C. The consensus panel proposed that the definition should be used for future clinical trials. The definition should be validated and the usability assessed during these studies.